Growth of seven perennial plant species adapted to the Brazilian Semi-Arid - Silva,Paulo Sérgio Lima e (2007)
Measuring plant height (y) and canopy diameter (x) in trees may not be an easy task, but stem diameter (z) can be more easily evaluated. This work's objective was two-fold: evaluate the growth of species adapted to the Brazilian Semi-Arid Region in the first two years of age, and obtain linear equations to estimate y and x from z, in those species. A random block design with four replications was employed. The values for x, z, and y were measured biannually from October/2003 to March/2005. Prosopis juliflora and Mimosa caesalpiniaefolia showed the highest stem diameter and plant height values, respectively, and both showed the highest canopy diameter. In the equations to estimate plant height from the stem diameter the value of the coefficient of determination (R²) ranged from 0.76 (Tamarindus indica and Leucaena leucocephala) to 0.92 (Prosopis juliflora and Azadirachta indica). In the equations that allowed to estimate the crown diameter from the stem diameter the R² value ranged from 0.70 (Leucaena leucocephala) to 0.92 (Azadirachta indica).